(3GNJUGQ dWGFa GdWQGFa hYhGQa GdeYGQas - (3eLghds
(3ChdgG (B:s
(3CeG HYO abO cfJ TQMJ QSGdI GdEeGe GdSeQbfOi ai GdGSJYGQGJ hSejJgG HdWGFa GdWQGFa hYhGQa GdeYGQa s
(3BNQgG (B:s
(3hGdQei JLQjOkG hGddg JYGdi CYde HGdUhGH s
(3dWGFa GdWQGFa TQM ajg GdeDda GdGSJYGQGJ ddSeQbfOi Ke GNJUQgs
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdHdGZIs